Interaction of 5′-Guanosine Monophosphate with Organotin(IV) Moieties: Synthesis, Structural Characterization, and Anti-Inflammatory Activity. (30th September 2012) - Nath, Mala; Singh, Hitendra; Eng, George; Song, Xueqing
Abstract : Reaction(s) of5 ′ -guanosine monophosphate (5 ′ GMP) with di- and triorganotin(IV) chloride(s) led to formation of organotin(IV) derivatives of general formulae, [R2 Sn(5 ′ -GMP) · H2 O] n and [(R′3 Sn)2 (5 ′ -GMP) · H2 O] n, where R = Me, n -Bu, and Ph; R′ = Me, i -Pr, n -Bu, and Ph; (5 ′ -GMP) 2− =5 ′ -guanosine monophosphate. An attempt has been made to prove the structures of the resulting derivatives on the basis of FT-IR, multinuclear 1 H, 13 C, and 119 Sn NMR and 119 Sn Mössbauer spectroscopic studies. These investigations suggest that both di- and triorganotin(IV)-5 ′ -guanosine monophosphates are polymeric in which (5 ′ -GMP) 2− is bonded through phosphate group resulting in a distorted trigonal bipyramidal geometry around tin. The ribose conformation in all of the derivatives is C 3′- endo, except diphenyltin(IV) and tri- i -propyltin(IV) derivatives where it is C 2′- endo . All of the studied derivatives exhibited mild-to-moderate anti-inflammatory activity ( 15.64–20.63% inhibition) at 40 mg kg −1 dose and LD50 values > 400 mg kg −1 in albino rats.